Answer:
-6
Step-by-step explanation:
The y-coordinate of B is 2. Adding -8 to it makes the y-coordinate of B' be -6.
2 -8 = -6
Answer:
Step-by-step explanation:
The given translation is
Which means that the original figure will be moved 3 units to the right and 8 units downwards.
Remember, when it comes to translations, when we subtract units to that means the figure will be moved rightwards. And if we subtract units from , that means the figure will be moved downwards.
So, the original figure has as vertex B(1,2). If we apply the transformation to its vertical cordinate , we would have
Therefore, the right answer is the third choice -6.
The sequence is decreasing so it is r<1, therefore it is converging
This is the formula for how to find the sum/limit of the convergence (or how to find a infinite geometric sequence): a1/(1-r)
a1=48
r=8/48=.167
Verifying r:
a1/r=48*.167=8.016=8
a1/r^2=48*.167^2=1.338672=1.34
4/3=1.33
(close enough)
Putting it into equation:
a1/(1-r)=48/(1-.167)=48/.833=57.62304922
Answer Choices:
A. Converges; 288/5
B. Converges; 0
C. Diverges
D. Converges; -12432
288/5=57.6
ANSWER IS A. Converges; 288/5
Answer:
.105
Step-by-step explanation:
Answer:
37°
Step-by-step explanation:
angle B = angle D (alternate angle)
2X = 74°
X = 37°
Answer:
29
Step-by-step explanation:
right in acellus
B - f(t) = 4(t − 1)^2 + 3; the minimum height of the roller coaster is 1 meter from the ground
C - f(t) = 4(t − 1)^2 + 2; the minimum height of the roller coaster is 2 meters from the ground
D - f(t) = 4(t − 1)^2 + 2; the minimum height of the roller coaster is 1 meter from the ground
Answer:
C - f(t) = 4(t − 1)^2 + 2; the minimum height of the roller coaster is 2 meters from the ground.
Step-by-step explanation:
Here we're asked to rewrite the given equation f(t) = 4t^2 − 8t + 6 in the form f(t) = a(t - h)^2 + k (which is known as the "vertex form of the equation of a parabola.") Here (h, k) is the vertex and a is a scale factor.
Let's begin by factoring 4 out of all three terms:
f(t) = 4 [ t^2 - 2t + 6/4 ]
Next, we must "complete the square" of t^2 - 2t + 6/4; in other words, we must re-write this expression in the form (t - h)^2 + k.
(To be continued)